Spelaeogammarus titan, a new troglobitic amphipod from Brazil (Amphipoda: Bogidielloidea: Artesiidae) - Senna, André R.; Andrade, Luiz F.; Castelo-Branco, Lucas P.; Ferreira, Rodrigo L. (Zootaxa, 2014)
A new troglobitic species of the amphipod family Artesiidae Holsinger, 1980 is described from a cave in the municipality of Santa Maria da Vitória, in the Brazilian state of Bahia, northeastern Brazil. Spelaeogammarus titan sp. nov. differs from the others in the genus by its body length, rising up to 18.3 mm, the antenna 1 with accessory flagellum 6-articulate, propodus of the first gnathopod 1.8 X longer than basis, the largest in the genus, coxa 5 with posterior lobe slightly concave, inner ramus of pleopods with 10 to 13 setae, outer ramus of uropod 3 with 22 simple setae, and telson with 1 apical plus 3 subapical stout setae in each lobe. With this study, the knowledge of Spelaeogammarus is improved to 5 species, all of them exclusive to caves in the northeastern Brazilian state of Bahia. A comparative table with the diagnostic characters of the species of Spelaeogammarus is provided.